Os impactos da Emenda Constitucional 95/2016 - teto de gastos - autonomia fiscal dos municípios da região metropolitana de Natal (funcional) - Silva, Josiane Gomes da (2024)
This work investigates the relationship between the fiscal regime and the financial autonomy of municipalities, following the implementation of Constitutional Amendment 95, better known as the Spending Ceiling Law. The study analyzes the impact of the amendment on the fiscal autonomy of municipalities in the Metropolitan Region of Natal, considering two sources of public policy funding: own revenue and intergovernmental transfers. The research hypothesis is that the implementation of the Spending Ceiling, together with the economic crisis, has had a negative impact on the collection of tax revenues and intergovernmental transfers, compromising the ability of municipalities to invest in public policies. The research seeks to contribute to the literature on fiscal regimes through an integrated analysis of the fiscal dynamics of municipal revenue, seeking a comprehensive understanding of the relationship between the fiscal regime and the fiscal autonomy of municipalities.